2016
DOI: 10.1016/j.stemcr.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

G9a and ZNF644 Physically Associate to Suppress Progenitor Gene Expression during Neurogenesis

Abstract: SummaryProliferating progenitor cells undergo changes in competence to give rise to post-mitotic progeny of specialized function. These cell-fate transitions typically involve dynamic regulation of gene expression by histone methyltransferase (HMT) complexes. However, the composition, roles, and regulation of these assemblies in regulating cell-fate decisions in vivo are poorly understood. Using unbiased affinity purification and mass spectrometry, we identified the uncharacterized C2H2-like zinc finger protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…zNCK2B knockdown and rescued embryos were assayed at 48 hpf (hours post fertilization) for midbrain GFP expression in the zebrafish enhancer trap line SAGFF(LF)223A, where GFP was inserted adjacent to lhx9 140 . Wild-type AB embryos were similarly injected with zNCK2B or control morpholino and mRNA, fixed at 48 hpf and assayed by whole mount in situ hybridization for lef1 expression as previously described 141 .…”
Section: Nck2 Function In Zebrafishmentioning
confidence: 99%
“…zNCK2B knockdown and rescued embryos were assayed at 48 hpf (hours post fertilization) for midbrain GFP expression in the zebrafish enhancer trap line SAGFF(LF)223A, where GFP was inserted adjacent to lhx9 140 . Wild-type AB embryos were similarly injected with zNCK2B or control morpholino and mRNA, fixed at 48 hpf and assayed by whole mount in situ hybridization for lef1 expression as previously described 141 .…”
Section: Nck2 Function In Zebrafishmentioning
confidence: 99%
“…The patterns of H3K9me1 or H3K9me2 are different during development, as there are either more mono-or dimethylations at H3K9 during the maturation of the auditory system (49). During the development of the zebrafish retina, EHMT2 expression and H3K9me2 markers have been noted to be closely associated (50). H3K9 methylation is a crucial event in reprogramming to pluripotency (51).…”
Section: Discussionmentioning
confidence: 99%
“…No Zfp644 -deficient mouse model has been generated so far, and only a fish model deficient for ZNF644 was previously described [22]. To investigate the molecular mechanism of ZNF644 , Olsen et al [22] prepared two different morphant models (MO) of znf644 , based on two znf644 isoforms (a and b) whose phenotype was severe and included changes in developing retina, midbrain, and eye size. Both znf644a-MO and znf644b-MO showed signs of microphthalmia and disrupted midbrain morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of ZNF644 in a cell culture results in reduced cell proliferation and higher sensitivity to replication stress as well as an increase of DNA damage in replicating cells [21]. Studies in fish showed that ZNF644 with G9a/GLP complex are responsible for histone methylation critical for gene silencing during neuronal differentiation in retinal neuron differentiation [22].…”
Section: Introductionmentioning
confidence: 99%